2019
DOI: 10.3389/fnmol.2019.00212
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Induced Pluripotent Stem Cells and Retinal Organoids From a Leber’s Congenital Amaurosis Patient With Novel RPE65 Mutations

Abstract: RPE65-associated Leber congenital amaurosis (LCA) is one of highly heterogeneous, early onset, severe retinal dystrophies with at least 130 gene mutation sites identified. Their pathogenicity has not been directly clarified due to lack of diseased cells. Here, we generated human-induced pluripotent stem cells (hiPSCs) from one putative LCA patient carrying two novel RPE65 mutations with c.200T>G (p.L67R) and c.430T>C (p.Y144H), named RPE65-hiPSCs, which were confirmed to contain the same mutations. The RPE65-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Here, we have analyzed the disease phenotype and expression profile within a staging system, which is largely consistent with their findings. Based on the staging system, the RO disease models established to date have all been early-or mid-stage (Parfitt David et al, 2016;Shimada et al, 2017;Teotia et al, 2017;Buskin et al, 2018;Deng et al, 2018;Guo et al, 2019;Huang et al, 2019;Li et al, 2019;Quinn et al, 2019). For example, in a previous RPGR-RP model established in our lab (Deng et al, 2018), impaired gene expression was found as early as D90, and impaired photoreceptor morphology was observed at approximately D150.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have analyzed the disease phenotype and expression profile within a staging system, which is largely consistent with their findings. Based on the staging system, the RO disease models established to date have all been early-or mid-stage (Parfitt David et al, 2016;Shimada et al, 2017;Teotia et al, 2017;Buskin et al, 2018;Deng et al, 2018;Guo et al, 2019;Huang et al, 2019;Li et al, 2019;Quinn et al, 2019). For example, in a previous RPGR-RP model established in our lab (Deng et al, 2018), impaired gene expression was found as early as D90, and impaired photoreceptor morphology was observed at approximately D150.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, retinogenesis can be recapitulated in ROs derived from pluripotent stem cells and analyzed by transcriptomic analysis (Kaewkhaw et al, 2015;Voelkner et al, 2016), and single-cell RNA-seq (Collin et al, 2019;Kim et al, 2019;Mao et al, 2019). Thus, patient-specific iPSCs combined with a three-dimensional (3D) culture system can generate unlimited cell sources for personalized drug testing and organ replacement (Shimada et al, 2017;Buskin et al, 2018;Deng et al, 2018;Guo et al, 2019;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, retinal organoids were also derived from a patient-specific iPSC line with compound heterozygous CRB1 mutations (c.1892A > G and c.2548G > A) [ 61 ]. To replicate the RPE65 -associated LCA and AlPL1 -LCA phenotype in a 3D in vitro system, patient-specific iPSCs were generated that were later used to generate organoids [ 62 , 63 ]. A similar study explored pathogenic splicing variants of the ABCA4 gene, a transporter protein responsible for Stargardt’s disease [ 64 ].…”
Section: The Rise Of Retinal Organoids–technical Development and Amentioning
confidence: 99%
“…To overcome these obstacles, in vitro studies evaluating the correct production and expression of the RPE65 protein (e.g., immunoblot, RT-qPCR, and RNA-sequencing), as well as its enzymatic activity, are advantageous. The evaluation of isomerhydrolase activity of RPE65 can be measured using iPS-derived retinal pigment epithelium (RPE) cells from patients, hES-derived RPE cells modified by site-directed mutagenesis, or transfected cells with a mutated RPE65 expression vector [14,25,68,69].…”
Section: Evaluation Of the Rpe65 Variants Pphe83leu And Pgly187glu mentioning
confidence: 99%
“…Recently, Li and colleagues (2019) presented new perspectives for personalized functional studies utilizing retinal organoids containing RPE and photoreceptor cells derived from human-induced pluripotent stem cells [69]. Despite the need for further studies to evaluate the ability of these organoids to mimic the phenotype and molecular aspects of the retina, the generation of these organoids can still enhance the study of cell replacement therapies.…”
Section: Evaluation Of the Rpe65 Variants Pphe83leu And Pgly187glu mentioning
confidence: 99%